Assessment of nurses’ knowledge about therapeutic play in pediatric services of a training and research hospital - TAŞÇI, Ayşenur; OZAKAR AKCA, Selen (Universa Medicina, 2025)
Background Hospitalization disrupts children’s lives and can produce feelings of anxiety, fear, or pain. Playing is an important part of children’s lives.It is necessary for nurses to provide holistic and quality care, including therapeutic play, which contributes to the recovery of children by relaxing them both physically and emotionally. The aim of this study was to determine the level of knowledge of pediatric nurses about therapeutic play and find out the relations of therapeutic play with nurses’age, educational level, marriage status, and length of employment. MethodsThis cross-sectional study was conducted with 126 pediatric nurses working in the pediatric service of a training and research hospital. The data of the study were collected with the “Nurse Introductory Information Form” and “Questionnaire for Determining the Level of Knowledge of Therapeutic Play”. Descriptive statistical tests and nonparametric tests were used to analyze the data. Statistical significance was set at p<0.05. ResultsIn this study, 88.1% of the nurses stated that they did not receive training in therapeutic play, and 79.4% stated that they wanted to receive training in therapeutic play. The nurses’ level of knowledge about therapeutic play significantly decreased with age and increased with educational level (p<0.05). ConclusIonsThe knowledge level of the nurses participating in the study about therapeutic play is above average, but is low regarding the integration of therapeutic play into care. It is recommended that nurses receive in-service training in therapeutic play.